Efektivitas PECS untuk Meningkatkan Kemampuan Bahasa Reseptif Anak dengan Autism Spectrum Disorder Usia 4-5 Tahun: The Effectiveness of PECS in Improving Receptive Language Skills in Children with Autism Spectrum Disorder Aged 4-5 Years - Sanjaya, Ridwan; Perdana Putra, Sinar; Nugroho, Setyadi (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The prevalence of Autism Spectrum Disorder (ASD) is increasing significantly in Indonesia, which affects children's communication skills and social-cognitive development. This study aims to test the effectiveness of the Picture Exchange Communication System (PECS) in improving receptive language skills in children with ASD aged 4–5 years at the Olan Development Center in Sragen. This quasi-experimental study, employing a one-group pretest–posttest design, involved five boys aged 4–5 years who were purposively selected. The PECS intervention consisted of 14 sessions, while receptive language skills were assessed using the Receptive Verbal Vocabulary Test (RVT) before and after the intervention. Data analysis included the Shapiro–Wilk normality test and a Paired Sample t-test to examine differences in pretest and posttest scores. The average receptive language score increased from 6.40 in the pretest to 14.20 in the posttest (mean difference = 7.80). The results of the Paired Sample t-test showed a significant increase (t = -4.033; df = 4; p = 0.016), indicating that the change in scores was not coincidental. Variations in responses between subjects were reflected in the posttest scores, which ranged from 4 to 26. PECS was effective in improving the receptive language skills of early childhood ASD children through a visual communication approach. It is recommended that PECS be implemented as part of speech intervention for children with ASD, as well as further research with larger samples, more extended follow-up periods, and control designs to strengthen the generalizability of the findings.